Overexpression of Long Non-Coding RNA POU3F3 in Esophageal Squamous Cell Carcinoma is Associated with TNM Stage and Family History - Halime Rahimnia; Abdolvahab Moradi; Naemeh Javid; Yasaman Fateri; Shabbou Bahramian; Zahra Roohinejad; Hossein Sabouri; Eisa Jorjani (Golestan University Of Medical Sciences, 2018)
Background and objectives: Esophageal cancer (EC) is the second most common gastrointestinal cancer, and esophageal squamous cell carcinoma (ESCC) is the dominant type of EC in Iran. One of the most important challenges in cancer management is the early diagnosis. As tumor suppressors or oncogenes, long non-coding RNAs (lncRNAs) play a vital role in tumor initiation, progression and metastasis. Recent studies have reported dysregulated expression of lncRNAs in different tumor tissues including ESCC, which may indicate its prognostic or diagnostic potential in ESCC. In this study, we investigated expression pattern of lnc-POU3F3 in ESCC. Methods: We performed quantitative real-time polymerase chain reaction to assess lnc-POU3F3 expression pattern in ESCC blood samples from 32 patients with ESCC and age- and sex-matched healthy controls. Results: Lnc-POU3F3 was significantly overexpressed in ESCC blood samples compared to normal samples. In addition, this overexpression had a significant correlation with family history (P=0.03) and TNM stage (P=0.02). Conclusion: According to the findings of the present study, lnc-POU3F3 may be used as a diagnostic biomarker for ESCC. However, studies with a larger sample size should be carried out to confirm this finding.